2022
DOI: 10.1002/ca.23935
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the nerves innervating the pelvic floor muscles: An application to pelvic pain treatment

Abstract: The aim of this study was to achieve accurate localization of the body surface position and depth of the center of the intramuscular nerve dense region (CINDR) of the pelvic floor muscles and to establish a target site for treating pelvic floor muscle spasm or weakness. Thirty‐six adult cadavers were studied in the prone position. To locate the CINDR of the levator ani and coccygeus muscles, horizontal (H) and longitudinal (L) reference lines were used. Sihler's staining revealed the intramuscular nerve dense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…INDRs may serve as an alternative target of BTX-A blocking injections for muscle spasticity (6)(7)(8). Therefore, INDR localization has become a research focus (9,10). Some studies revealed that the excitation of muscle spindles could exacerbate muscle spasticity via the α-γ loop (11) and that muscle spindle abundance is high in INDRs but are not evenly distributed (12).…”
Section: Introductionmentioning
confidence: 99%
“…INDRs may serve as an alternative target of BTX-A blocking injections for muscle spasticity (6)(7)(8). Therefore, INDR localization has become a research focus (9,10). Some studies revealed that the excitation of muscle spindles could exacerbate muscle spasticity via the α-γ loop (11) and that muscle spindle abundance is high in INDRs but are not evenly distributed (12).…”
Section: Introductionmentioning
confidence: 99%
“…However, the INDR is a broader region and requires a high‐dose injection of BTX‐A, which can produce side effects such as antibodies and muscle fibrosis (Kroumpouzos et al., 2021 ). It has been suggested that the muscle spindle plays a vital role in muscle spasticity and that BTX‐A could maximise the blockade of intrafusal muscle fibres and minimise the effects on extrafusal muscle fibres (He et al., 2022 ; Hu et al., 2022 ; Phadke et al., 2013 ). Muscle spindles grow at different rates and are highly abundant in the INDR but are not uniformly distributed (Banks, 2006 ).…”
Section: Introductionmentioning
confidence: 99%